2012
DOI: 10.1186/1745-6215-13-244
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pharmaceutical care on the quality of life of patients with Chagas disease and heart failure: randomized clinical trial

Abstract: BackgroundPharmaceutical care is the direct interaction between pharmacist and patient, in order to improve therapeutic compliance, promote adequate pharmacotherapeutic follow-up, and improve quality of life. Pharmaceutical care may be effective in reducing complications and in improving the quality of life of patients with chronic diseases, like Chagas heart disease, while bringing a positive impact on health system costs. The morbidity and mortality indexes for patients with Chagas heart disease are high, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
1
7
0
1
Order By: Relevance
“…One of the few randomised clinical trials in the area of social pharmacy carried out among patients with Chagas' disease complicated by HF showed a significant improvement of life of patients under pharmaceutical care as a result of reducing the number of drug problems and improved adherence [15]. Similar conclusions can be drawn from another study, which included patients with type 2 diabetes [16].…”
Section: Looking For a Common Denominator -Health-related Quality Of supporting
confidence: 58%
“…One of the few randomised clinical trials in the area of social pharmacy carried out among patients with Chagas' disease complicated by HF showed a significant improvement of life of patients under pharmaceutical care as a result of reducing the number of drug problems and improved adherence [15]. Similar conclusions can be drawn from another study, which included patients with type 2 diabetes [16].…”
Section: Looking For a Common Denominator -Health-related Quality Of supporting
confidence: 58%
“…Indeed, there are now pharmaceutical trials in patients with heart failure where quality of life is the primary, rather than secondary, outcome. 24 Our findings are important from a clinical perspective in that they suggest that children at greatest risk of clinical decline can be identified by these measures and warrant increased monitoring; and that formal functional status measurement should be integrated into prognostic assessment, similar to such increasing practice in adult care. 25 Uzark et al 26 demonstrated the clinical utility of such assessment in the setting of a pediatric cardiology clinic.…”
Section: Discussionmentioning
confidence: 78%
“…[133] Multidisciplinary approach of heart failure patients, including cardiac rehabilitation and pharmaceutical care, may be helpful in improving symptoms and quality of life in Chagas disease patients. [134,135]…”
Section: Heart Failure: Advances In Pharmacological Treatmentmentioning
confidence: 99%